Pengaruh Upah Minimum, Tingkat Pengangguran Terbuka, Dan Pendidikan Terhadap Jumlah Penduduk Miskin Di Jawa Timur Tahun 2014-2023 - Rahma Amalia; Lastri Khafiah; Tahta Rajani; Muhammad Kurniawan (STIKes Ibnu Sina Ajibarang, 2024)
Poverty is a complex and multifaceted issue faced by various countries, including Indonesia. East Java, as one of the provinces with the largest population in Indonesia, still has a relatively high poverty rate. Minimum wage, open unemployment rate, and education are three important factors believed to influence the poverty rate. Minimum wage is expected to increase the purchasing power of poor people, while high open unemployment rate and low education levels can exacerbate poverty. This study aims to analyze the influence of Minimum Wage, Open Unemployment Rate, and Education on the Number of Poor People in East Java Province. The independent variables are Minimum Wage, Open Unemployment Rate, and Education, and the dependent variable is the Number of Poor People. This research uses secondary data in the form of time series for 10 years, from 2014 to 2023. The data was obtained from Statistics Indonesia (BPS). The research method is quantitative with data analysis using classical assumption tests (Normality Test, Multicollinearity Test, Heteroscedasticity Test, Autocorrelation Test), multiple linear regression, and statistical tests (Coefficient of Determination Test (R2), T-Test, and F-Test) using Eviews - 10. The partial regression coefficient results show that minimum wage and education do not have a significant effect on the number of poor people in East Java, while the open unemployment rate has a significant effect on the number of poor people in East Java.